The Role of the Media in Creating Earnings Informativeness: Evidence from Spain. Issue 3 (July 2018) - Peña-Martel, Devora; Pérez-Alemán, Jerónimo; Santana-Martín, Domingo Javier
We analyse the effect of the media on the informativeness of accounting earnings. We collected news articles on a sample of non-financial listed firms over the 1996 to 2014 period in Spain, a country characterised by the widespread presence of dominant owners. Our results indicate that disclosing information through financial media coverage in newspaper articles positively affects earnings informativeness. Moreover, results show that publishing media news reports which have a negative tone has a positive effect on the informativeness of accounting earnings. Results suggest that the media serves as an effective external corporate governance mechanism in improving the informativeness of accounting earnings within the context of Spain.